ANALISIS DIAGNOSIS KESEHATAN KEPEMIMPINAN DI LEMBAGA DIKLAT - Dewi Utari Anggraen (Universitas Pendidikan Indonesia, 2021)
Leadership in an organization has a major influence on achieving its goals. The main research question of this study was thus whether the leadership in the organization is running well. Hence, an instrument is required. That leads to why this author was interested in researching it with the title